The Impact of Ocean‐Wave Coupling on the Upper Ocean Circulation During Storm Events. Issue 6 (16th June 2021) - Bruciaferri, D.; Tonani, M.; Lewis, H. W.; Siddorn, J. R.; Saulter, A.; Castillo Sanchez, J. M.; Valiente, N. G.; Conley, D.; Sykes, P.; Ascione, I.; McConnell, N.
Abstract: Many human activities rely on accurate knowledge of the sea surface dynamics. This is especially true during storm events, when wave‐current interactions might represent a leading order process of the upper ocean. In this study, we assess and analyze the impact of including three wave‐dependent processes in the ocean momentum equation of the Met Office North West European Shelf ocean‐wave forecasting system on the accuracy of the simulated surface circulation. The analysis is conducted using ocean currents and Stokes drift data produced by different implementations of the coupled forecasting systems to simulate the trajectories of surface (iSphere) and 15 m drogued (SVP) drifters affected by four storms selected from winter 2016. Ocean and wave simulations differ only in the degree of coupling and the skills of the Lagrangian simulations are evaluated by comparing model results against the observed drifter tracks. Results show that, during extreme events, ocean‐wave coupling improves the accuracy of the surface dynamics by 4%. Improvements are larger for ocean currents on the shelf (8%) than in the open ocean (4%): this is thought to be due to the synergy between strong tidal currents and more mature decaying waves. We found that the Coriolis‐Stokes forcing is the dominant wave‐current interaction for both type of drifters; for iSpheres the secondary wave effect is the wave‐dependent sea surface roughness while for SVPs the wave‐modulated water‐side stress is more important. Our results indicate that coupled ocean‐wave systems may play a key role for improving the accuracy of particle transport simulations. Plain Language Summary: Precise data on ocean surface velocities are of fundamental importance for several human activities, such as search and rescue or oil spill and plastic dispersal monitoring and control operations. Measurements of the surface dynamics are usually scarce both in time and space and typically data from numerical models are used instead. Traditionally, ocean and wave‐induced currents are computed by ocean and wave models which are run independently from each other. In this study, we investigate the impact on the predicted surface circulation of using a coupled system where the ocean model receives the feedbacks of three wave‐related processes. Since during storm conditions large waves can exert a strong control on the upper ocean circulation, we focus our study on extreme events. Our results show that the coupled system generally improves the accuracy of the predicted surface circulation by 4 %, with improvements larger on the shelf than in the open ocean. Key Points: Impact of ocean‐wave coupling on Lagrangian trajectories during storm events is assessed and analyzed Coupled system simulates more accurate surface dynamics than uncoupled models with larger improvement on the shelf The Coriolis‐Stokes force is the dominant wave interaction for both surface and 15 m drogued drifters